Temporality, genre and experience in the Age of Shakespeare forms of time - Shohet, Lauren (The Arden Shakespeare, 2018)
Focusing on Shakespeare and his contemporaries, these original essays by leading scholars explore how theatrical, aesthetic, and linguistic forms engage early modern experiences of temporality. Encompassing comedy, tragedy, history, and romance, some contributions consider how different models of pastness, presentness, sequentiality, memory, and historical meaning underwrite particular representational practices. Others, conversely, investigate how aesthetic forms afforded diverse ways for early-modern people to understand or experience time - and how this can impact us today.